KAJIAN PERPUSTAKAAN KHUSUS DAN SUMBER INFORMASI DI INDONESIA - Tambunan, Kamariah (BACA: Jurnal Dokumentasi dan Informasi, 2013)
This study tries to know the map of special libraries and information sources in Indonesia. Publication which examined are Directory of Special Libraries and Information Sources in Indonesia which published in 1981, 1985, 1990, 1995, 2000, and 2005. Data was collected by rewrite of each title of the library, address or city also province, field or subject, and established year. Total of the special libraries base on city (libraries address), field or subject, and established year then calculated and presented in form of tables and hystograms. The result shows that total of special libraries and information sources in Indonesia increase year by year. The last publication in 2005 registered as many as 994 of libraries which reside in 32 provinces (136 cities) in Indonesia. Base on the total that registered, 668 libraries are in Jawa Island (62 cities), and others 326 libraries are in outside Jawa Island (74 cities). The most of special libraries with subject of religion (143 libraries) and economics (140 libraries), then social, agriculture, education, law, and medicine. The author also found that there are 3 oldest special libraries which were established in 1842, 1886, and 1887, while the youngest library was established in 2004.